2011
DOI: 10.1113/expphysiol.2011.059147
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vascular and core temperature responses to sustained cold exposure in hypoxia

Abstract: We tested the effect of hypoxia on cutaneous vascular regulation and defense of core temperature during cold exposure. Twelve subjects had two microdialysis fibres placed in the ventral forearm and were immersed to the sternum in a bathtub on parallel study days (normoxia and poikilocapnic hypoxia with an arterial O 2 saturation of 80%). One fibre served as the control (1 mm propranolol) and the other received 5 mm yohimbine (plus 1 mm propranolol) to block adrenergic receptors. Skin blood flow was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…The lack of difference in sweating but altered cutaneous blood flow responses during hypoxia in this study may seem counterintuitive, but other researches has shown that variations in regional sweating are not explained by local variations in cutaneous blood flow . The slightly reduced core temperature elevation during heating in Hypoxia in this study despite similar heating protocols (e.g., similar mean skin temperatures and duration of heating) is intriguing and is consistent with previous research that reported lower core temperatures during combined cold and hypoxic stress . However, similar local sweat rates and similar or lower local cutaneous blood flow responses would not contribute to a lower core temperature elevation during heating in hypoxia.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of difference in sweating but altered cutaneous blood flow responses during hypoxia in this study may seem counterintuitive, but other researches has shown that variations in regional sweating are not explained by local variations in cutaneous blood flow . The slightly reduced core temperature elevation during heating in Hypoxia in this study despite similar heating protocols (e.g., similar mean skin temperatures and duration of heating) is intriguing and is consistent with previous research that reported lower core temperatures during combined cold and hypoxic stress . However, similar local sweat rates and similar or lower local cutaneous blood flow responses would not contribute to a lower core temperature elevation during heating in hypoxia.…”
Section: Discussionsupporting
confidence: 86%
“…With acute cold exposure in a laboratory setting, Simmons et al. [70–72] studied the effect of hypoxia on cutaneous vascular conductance during cold exposure. Data from these three studies are mixed, suggesting both increased and decreased cutaneous vasoconstriction in the forearm.…”
Section: Longitudinal Field Studiesmentioning
confidence: 99%
“…Based on field acclimation studies, one intriguing possibility is that hypoxic exposure itself, irrespective of cold exposure, potentiates CIVD response and local thermal response to cold. With acute cold exposure in a laboratory setting, Simmons et al [70][71][72] studied the effect of hypoxia on cutaneous vascular conductance during cold exposure. Data from these three studies are mixed, suggesting both increased and decreased cutaneous vasoconstriction in the forearm.…”
Section: Longitudinal Field Studiesmentioning
confidence: 99%
“…In cold environment, practitioners are more liable to make mistakes or wrong cognitive choices, as their decision-making deteriorates (e.g., rugby players dropping the ball on the coldest match days) [123], potentially increasing the risk of being injured as well. Prolonged exposition to cold environments can cause hallucinations, while the combination of cold and hypoxia exacerbate the magnitude of physiological adaptations [123]; for instance, hypoxia is known to increase cutaneous vasoconstriction during prolonged cold exposure [129]. Finally, "cold urticarial" arises during re-warming after cold exposure.…”
Section: Coldmentioning
confidence: 99%